Research and support for knowledge transfer in the ATHENA Twinning project: Remote sensing for cultural heritage - Hadjimitsis, Diofantos G.; Agapiou, Athos; Lysandrou, Vasiliki; Nisantzi, Argyro; Christofe, Andreas; Tzouvaras, Marios; Papoutsa, Christiana; Mamouri, Rodanthi-Elisavet; Mettas, Christodoulos; Evagorou, Evagoras G.; Themistocleous, Kyriacos; Lasaponara, Rosa; et al. (My University, 2018)
This paper presents some of the outcomes of an on-going Horizon 2020 Twinning project, under the acronym ATHENA. The project aims to establish a “Remote Sensing Science Center for Cultural Heritage” in Cyprus. The Center foresees to support the current Cultural Heritage (CH) needs through the systematic exploitation of Earth Observation technologies. For the establishment of the center, the existing Remote Sensing and Geo-Environment Research Laboratory of the Eratosthenes Research Center (ERC) based at the Cyprus University of Technology (CUT), is twinned with internationally-leading counterparts from the EU, the National Research Council of Italy (CNR, through IMAA and IBAM) and the German Aerospace Centre (DLR). Through this network, the ATHENA twinning project strengthens the remote sensing capacity in cultural heritage at CUT’s ERC.
Keywords: Remote sensing; Cultural Heritage; Cyprus; ATHENA project